Arte e psicanálise:a relação da arte com as formações do inconsciente através da obra de Sigmund Freud - Chignoli, Giovanna Juliani (Universidade Federal de São Carlos, 2021)
The present work aims to analyze Sigmund Freud’s work in order to characterize the artistics creations as a result of the unconscious psychic formations, as are the dream, the lapse, the freudian slip and the organization of neurosis. It being the major difference between they [the unconscious psychic formations], the communicability - given by a innumerable number of distocions - that the unconscious contents acquire when express through artistic creation
Art and psychoanalysis: the relation of art with unconscious formations through Sigmund Freud’s work
Keywords: Arte; Psicanálise; Art; Psychoanalysis; CIENCIAS HUMANAS::PSICOLOGIA